Efecto de métodos de desinfección fúngica como tratamiento postcosecha sobre la calidad de la pitahaya roja (Hylocereus Undatus) para exportación - Vélez Mendoza, Evelyn Pierina (2025)
The research aimed to evaluate the effect of physical, chemical, natural, and conventional fungal disinfection methods. Three response variables were studied: contaminated fruit area, disinfectant treatment efficacy percentage, and peduncle damage. Each dragon fruit represented an experimental unit, and the variables were statistically analyzed using two designs: a completely randomized block design for the contaminated area variable, and a completely randomized unifactorial design for the disinfectant efficacy percentage and peduncle damage variables. The results showed no significant differences among treatments; however, when expressed in a dot plot, the thermal treatment presented an average efficacy of 31.33% and an appearance index of 2.33 for the last two variables, which were favorable but not sufficient to establish it as the best treatment. The fungus causing the damage in the red dragon fruits for export was identified as belonging to the genus Rhizopus, and none of the proposed disinfection methods (chemical, hydrothermal, or natural) demonstrated a significant reduction in any of the response variables.